The Compensation for Losses to Indigenous Peoples Due to the Arctic Industrial Development in Benefit Sharing Paradigm - Violetta Gassiy; Ivan Potravny (Resources, 2019)
This article discusses the results of research on the benefit sharing system in Russia focusing on compensation of losses to indigenous peoples due to industrial development in the Arctic. The authors analyzed a Russian case-study on the economic mechanisms of coordination and harmonization of multi-vector and conflicting interests in the process of industrial development of traditional lands. The developed recommendations will allow, on the one hand, compensating the losses of the indigenous communities, and, on the other hand, to engage indigenous peoples in the process of environmental management and socio-economic development of their territories. The object of the research was the Republic of Sakha and the indigenous communities of the remote Anabar region. The calculation of losses was considered. The authors suggest using this tool for the traditional lands development, because it helps to define fair compensation due to project impacts and to form a fund for sustainable community development. The considered project was exploring and extracting placer diamonds in Polovinnaya River in Yakutia. This paper also presents the social poll results organized in the indigenous communities in 2017. The results helped to formulate the recommendations for the business on benefit sharing agreements with Anabar communities.